Analisis Faktor Internal Penyebab Kesulitan Belajar Ditinjau dari Motivasi Belajar dan Minat Belajar - Sulastri Latief; Ani M. Hasan; Nur Mustaqimah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze internal factors causing students' learning difficulties in biology, specifically from the perspective of motivation and interest. The study was conducted at SMA Negeri 2 Gorontalo, with 29 students in grades XI-3 in the 2025/2026 academic year as subjects. The method used was descriptive quantitative, with data collection techniques using questionnaires, observations, and interviews. The results showed that students' learning motivation was high, with an average percentage of 78%, while their learning interest was also high, with an average percentage of 79%. However, learning difficulties were still found in some students, influenced by low self-discipline and a lack of independent study habits outside of school hours. These findings indicate that high motivation and interest in learning are not fully accompanied by effective and consistent learning behaviors. Therefore, learning efforts are needed that focus not only on increasing motivation and interest but also on strengthening students' learning independence and discipline to minimize learning difficulties in biology.